Patient- and lesion-tailored algorithm of endovascular treatment for arterial occlusive disease of extracranial arteries supplying the brain: safety of the treatment at 30-day follow-up - Latacz, Paweł; Simka, Marian; Brzegowy, Paweł; Janas, Piotr; Kazibudzki, Marek; Pieniążek, Piotr; Ochała, Andrzej; Popiela, Tadeusz; Mrowiecki, Tomasz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2017)
Introduction: Although surgical endarterectomy remains the treatment of choice for carotid artery stenosis, stenting plays an important role as an alternative treatment modality, especially in high-risk patients. The actual safety profile associated with stenting procedures is probably better than that reported by randomized controlled trials. Aim : To assess the safety of stent implantations in extracranial arteries supplying the brain, and also to identify risk factors associated with this procedure. Material and methods: This was a post hoc analysis, with 30-day follow-up. We analyzed the results of treatment of 372 patients who underwent 408 procedures, 197 such procedures in asymptomatic, and 211 in symptomatic individuals. Stenting procedures were performed using a technique and armamentarium which were tailored to the type and anatomy of lesions. Results : There were 6 (1.5%) strokes, including 2 (0.5%) major strokes, 1 ipsi- and 1 contralateral, and 4 (1.0%) minor strokes. In asymptomatic patients there was 1 (0.3%) minor stroke. Transient ischemic attacks occurred in 5 (1.2%) patients. There were 2 (0.5%) non-STEMI myocardial infarctions and 2 (0.5%) non-stroke related fatalities. Risk factors of these adverse events were diabetes mellitus, lesions localized in a tortuous segment of the artery, embolic material in the filter and bilateral stenoses of carotid arteries. Additional risk factors in asymptomatic patients were renal impairment and advanced coronary artery disease; and in symptomatic patients, grade 3 arterial hypertension, dislipidemia, cigarette smoking and lesions requiring predilatation. Conclusions : Stenting procedures of extracranial arteries supplying the brain, which are tailored to the type and anatomy of lesions, seem to be relatively safe.